Rooperol tetraacetate decreases cytokine mRNA levels and binding capacity of transcription factors in U937 cells - A. Guzdek; H. Rokita; J. Cichy; A. C. Allison; A. Koj (Hindawi Limited, 1998)
We have previously described inhibition of the synthesis of three acute-phase inflammatory cytokines in human and rat macrophages by acetate esters of rooperol, a dicatechol of plant origin. Analysing the mechanism of anticytokine activity of rooperol, we compared levels of TNF α , IL-1 β and IL-6 mRNAs in the human promonocytic U937 cell line pretreated with phorbol myristate acetate (PMA) and incubated with rooperol tetraacetate (RTA) alone or in combination with LPS (500 ng/ml). It was found that 10 μM RTA decreased the levels of cytokine mRNAs both in the presence and absence of LPS, suggesting pretranslational inhibition of cytokine synthesis. Electrophoretic mobility shift analysis (EMSA) showed that RTA may influence cytokine mRNA expression by decreasing the binding activity of transcription factors NF- κB and AP-1.